A CLASS OF GROWTH MODELS RESCALING TO KPZ. (19th November 2018) - HAIRER, MARTIN; QUASTEL, JEREMY
Abstract : We consider a large class of 1+1 -dimensional continuous interface growth models and we show that, in both the weakly asymmetric and the intermediate disorder regimes, these models converge to Hopf–Cole solutions to the KPZ equation.